Power Structures in După gâşte (After Geese) by Lucian Dan Teodorovici - Zsuzsa Tapodi; Ingrid Tomonicska (Acta Universitatis Sapientiae: Philologica)
The distribution of power is present at all levels of our existence: race, religion, ethnicity, culture, military level, politics, and economics. The power structures have never been based on equality because there is always a person or a group that wants to impose his/her/their view upon others. The present study follows these balances at multiple levels: from the point of view of the macro- (societal) and the micro- (individual/private) sphere, but also from the perspective of ethnicity and gender as they are represented in După gâşte (After Geese) by Lucian Dan Teodorovici. The main stream of the short story has a rather simplistic pretext – the theft of some geese by the Gypsies in a Romanian village –, which masterly introduces us to the problem of power structures.